Determinan laba bersih pada perusahaan sub sektor makanan dan minuman yang terdaftar di Bursa Efek Indonesia - Yuana Rizky Octaviani Mandagie (LPMP Imperium, 2022)
This study aims to test the influence of production costs, promotional costs and sales on net profit. The population of this study is food and beverage companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. The sample count of this study is 11 companies. The analysis conducted in this study is descriptive statistical test, normality test and hypothesis test. The measuring instrument used for this analysis is spss version 25 program. The results showed that production costs and sales had an effect on net profit, while promotional costs had no effect on net profit with a probability.